Halal Awareness : Pengaruhnya Terhadap Keputusan Pembelian Konsumen Shopee dengan Religiositas Sebagai Variabel Moderasi - Juliana Juliana; Muhamad Wafa Rizaldi; Rumaisah Azizah Al-Adawiyah; Ropi Marlina (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2022)
Purpose- This study aims to determine and analyze the effect of the halal awareness variable on Indonesian Muslim consumers on purchasing decisions at Shopee with religiosity as a moderating variable. Design/Methodology/Approach – Using quantitative descriptive methods, this study analyzes responses to questionnaires distributed to 264 respondents from Indonesia. To prove this hypothesis, the data collected was analyzed by partial least squares (SEM-PLS) using SmartPLS. Findings – This research shows that the Halal Awareness variable has a significant and significant effect on product purchasing decisions at Shopee with religiosity as a moderating variable. This finding confirms that halal awareness and religiosity factors are very important in encouraging Muslim consumers in Indonesia to make decisions to purchase halal products at Shopee. Practical Implication – In order to improve purchasing decisions in buying halal products in e-commerce, especially Shopee. then the role of the government will be very necessary in socializing and re-promoting the concept of halal lifestyle, especially in buying online products in e-commerce optimally in various platforms, such as social media, seminars, workshops and several other media. Then, business actors in various fields of goods production with online and e-commerce sales media are also required to increase awareness to support and develop halal products by certifying halal products, halal labeling and seeing the importance of halal products to become one of the promising types of products. and sell well in the market and also safe for consumers. Originality/Value – This study is the first to examine the effect of halal awareness on purchasing decisions of Indonesian Muslim consumer products at Shopee with religiosity as a moderating variable. This study succeeded in revealing the strengths and weaknesses of religiosity in influencing halal awareness of product purchasing decisions at Shopee.